Prediction of Electrical Arc and Fire Prevention in Electrical Systems - Bohaimed, Al-Kunouz (2019)
In recent days, electrical power consumption in households has increased tremendously. With the increase in demand for electricity, there also comes a proportional increase in electrical tribulations. Problems with electrical wirings may lead to arc faults which are one of the main causes of electrical fires in buildings. This project proposes a design of an arc fault protection system for low voltage systems. A mathematical arc model was developed using MATLAB’s Simulink. An arc generating device was then built in order to practically test the functionality of the protection system. A block diagram of the main protection system is split into a few essential subsystems. It begins with three sensing circuits that act as inputs to a microcontroller. These circuits are the zero-crossing detector circuit, current amplifier, and Butterworth filter with minimum detection. Since arcing occurs mainly by the zero-crossing, the zero-crossing detector circuit can be used to see if there is a high probability of arcing occurring. The current amplifier informs the microcontroller if a load is connected or if there is simply noise on the line. Arcing also produces frequencies in the range of 10 to 13 MHz, as such the Butterworth filter will filter out these signals and pass them through a minimum detection circuit which returns a high or low to the microcontroller based on the presence of high frequency signals. The microcontroller analyzes the input data and sends a tripping signal to the current generator that steps it up in order to trigger the circuit breaker. All these components when brought together make up a comprehensive and efficient arc fault protection system."